Bridging cognitive and literacy gaps: designing a working memory-based reading support program for students with dyslexia - Ozer Sanal, Seda (Springer, 2026)
Supporting the social participation and independent living of all students with special needs is crucial. It is known that various technologies and methods have a positive impact on supporting the reading skills of individuals diagnosed with reading difficulties (dyslexia). However, there is a clear need to develop designs appropriate to the cognitive structures of dyslexic students and provide them with the most appropriate learning materials and environments. Therefore, this study focuses on improving reading skills through a working-based reading-supported reading intervention program. The study involves two sequential processes: design-based research (DBR) and single-subject experimental research. The DBR process included two main phases: Foundational design inquiry and empirical design refinement. The DBR process involved detailed literature analysis, focus group interviews with special education teachers, and Delphi rounds with expert academics. After reaching the final design principles, a single-subject experimental process was conducted to examine the program's effectiveness on the reading skills of students with dyslexia. Thematic analysis was used for qualitative data analysis, while graphs, percentages, and Tau-U effect size values were used for quantitative data analysis. This study has contributed to teaching practices and materials for students with dyslexia in national and international contexts by revealing how special education teachers should prepare digital materials for students with dyslexia.
Keywords: Working Memory; Reading; Dyslexia; Literacy Development; Design Based Research; Single Case Design